Nueva España versus México: historiografía y propuestas de discusión sobre la Guerra de Independencia y el Liberalismo doceañista - Chust, Manuel; Serrano, José Antonio (Revista Complutense de Historia de América, 2008)
The different interpretations about the war of independence in Mexico have been treated from classical propositions of the Patriot History. In this essay, we try to radiography the mexican independence from the absolut prism of the mexican Revolution as the big happening which irradiated the history and the historiography of the Nineteenth century. We also make a review of other propositions and, finally, our contribution about the importance of the doceañista liberalism in the consequence of the construction of the mexican Nation-state.